DIGITAL TRANSFORMATION OF BANKING IN UKRAINE (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Introduction. The article is devoted to studying the essence of the digital transformation of banking in Ukraine, key trends, and changes in the market arising from the digitalization of banks' products and services, including changes and trends under martial law.The purpose of the article. The article aims to study the current trends and prospects of digital transformation of banking in Ukraine, particularly under martial law.Results. The authors consider an approach to defining the main aspects of the essence of "digital transformation" of banking institutions in the context of comparison with "digitization" and "digitalization".The authors analyze the main trends in the digital transformation of banking activities in Ukraine and identify significant market changes resulting from the digitalization of banking products and services.The authors also consider the critical steps of the National Bank of Ukraine as a market regulator concerning digital transformation. In particular, the authors analyze essential legislative changes that contribute to developing the digital transformation of banking in Ukraine.The authors also showed that digital transformation is one of the drivers of the banking market development, which creates an urgent need for banks to modernize their business strategies with a focus on digitalization.Conclusions. It is concluded that today, the use of innovative technologies in banking significantly changes the payment infrastructure. Despite the daily challenges and threats, the Ukrainian market shows significant steps and prospects in using and developing financial technologies and innovations. Therefore, for traditional banking institutions to remain competitive in the market and provide services that will meet customers' growing needs, banks need to completely rethink their business strategy with a focus on digital transformation.
Keywords: banking, banking institutions, digitization, digitalization, digital transformation.